Myxoedemic coma: an uncommon presentation of Sheehan syndrome - Rawat, Ramakant; Rawat, Rajani; Singh, P. S.; Kumar, Manoj (International Journal of Research in Medical Sciences, 2017)
This is a rare case of a 35 year old multiparous female who presented with electrolyte abnormality, hyponatremia in a setting of seizure and moderate pallor. She had a significant past history of childbirth complicated with post-partum haemorrhage after which she developed secondary amenorrhoea and lactation failure. Workup showed suppressed levels of all pituitary hormones and was treated as myxoedemic coma. A diagnosis of Sheehan’s syndrome presenting as myxoedemic coma - a rare but emergency presentation was made.